2018
DOI: 10.1080/15592294.2018.1475978
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and cord blood DNA methylation: new insight on sex differences and effect modification by maternal folate levels

Abstract: Maternal smoking during pregnancy may affect newborn DNA methylation (DNAm). However, little is known about how these associations vary by a newborn's sex and/or maternal nutrition. To fill in this research gap, we investigated epigenome-wide DNAm associations with maternal smoking during pregnancy in African American mother-newborn pairs. DNAm profiling in cord (n = 379) and maternal blood (n = 300) were performed using the Illumina HumanMethylation450 BeadChip array. We identified 12 CpG sites whose DNAm lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Interestingly, the impact of prenatal cigarette smoke on DNA methylation may be gender-specific. It was shown that the male fetus is more susceptible to maternal smoking than the female [110], and the alteration of DNA methylation in the differentially methylated region (DMR) of the IGF2 gene was more notable among newborn boys than girls [105], whereas Bouwland-Both reported an adverse result [111]. Moreover, a study has shown that maternal smoking showed a much stronger impact on offspring methylation intensity than paternal smoking [15] (Table 1).…”
Section: Prenatal Environmental Pollution and Epigenetic Dysregulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the impact of prenatal cigarette smoke on DNA methylation may be gender-specific. It was shown that the male fetus is more susceptible to maternal smoking than the female [110], and the alteration of DNA methylation in the differentially methylated region (DMR) of the IGF2 gene was more notable among newborn boys than girls [105], whereas Bouwland-Both reported an adverse result [111]. Moreover, a study has shown that maternal smoking showed a much stronger impact on offspring methylation intensity than paternal smoking [15] (Table 1).…”
Section: Prenatal Environmental Pollution and Epigenetic Dysregulationmentioning
confidence: 99%
“…Dynamic processes of epigenetic reprogramming in male and female genomes exhibit dramatic differences [14, 20] and this includes changes to the epigenome in their embryonic stem cells [249]. As aforementioned, male fetus has been observed a higher susceptibility to maternal smoking than the female [110]. Developmental exposure to vinclozolin [156] and BPA [146148] has been shown a transgenerational inheritance of aberrant methylation patterns through the male germ line.…”
Section: Prenatal Environmental Pollution and Epigenetic Dysregulationmentioning
confidence: 99%
“…[15]. Despite the common use of CB as an epigenetic surrogate of neonates, several published studies involve the correction of epigenetic data based on cell type population of CB specimens using microarray [4850], and the requirement of such correction in the future studies may introduce significant complexity into CB-based epigenetic studies using other methods. Recently, Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Demethylation of AHRR in the cord blood of children with prenatal smoking exposure is broadly reported. One recent study further discovered the interactive effect of maternal smoking and high folate level, suggesting that adequate maternal folate levels attenuate the impact of smoking on the hypomethylation of AHRR [118]. As these studies mature and elaborate on these co-exposure effects, we may be able to better classify and understand the epigenetic plasticity to the complexity and mixture of exposures.…”
Section: Challenges and Outlookmentioning
confidence: 99%